Cálculo de tamaño muestral y precisión para estudios epidemiológicos: desarrollo e implementación del paquete Calculadora Prevalencia en R - Vera-Ponce, Víctor Juan (2025)
Determining sample size and assessing precision are essential components of epidemiological research. This article presents Calculadora Prevalencia, an R-based tool designed to facilitate these calculations by incorporating both methodological and logistical factors. The calculator supports various scenarios, including finite and infinite populations, stratifed sampling, and adjustments for instrument sensitivity and specificity. Its utility is demonstrated through practical examples across diverse contexts: infinite urban populations, finite rural populations, stratifed university sampling, and the analysis of existing datasets. The tool also addresseslogistical considerations, estimating the number of subjects to contact based on rejection and eligibility rates, and projecting expected feldwork duration. Its versatility enables both prospective planning and retrospective data evaluation, while the innovative inclusion of logistical components offers a realistic perspective on the resources needed to carry outsuccessful epidemiological studies.